Polyaniline as Novel Polymer Materials for Dry Electrode- Based Electrocardiography (ECG) - Jeffry Omega Prima; Bayu Pamungkas; Nugraha -; Suprijanto - (National Research and Innovation Agency, 2018)
Electrocardiography (ECG) has been instrumental for early detection of cardiovascular anomalies. In this research, we successfully prototyped and evaluated the performance of a novel dry electrode as ECG sensor. Copper was selected as dry electrode material due to its good balance between conductivity and affordability. Polyaniline was used as a conductive coating to facilitate the conversion of ionic currents from the human body into electrical currents in electronic circuits. The coating was carried out via electrodeposition technique. Optimal electrodeposition time of 20 min using acetic acid as a dopant was established. This yields in the dry electrode with comparable performance to the certified wet electrode currently available in the market, shown by PQRST signal correlation between dry electrodes (this study) and the wet electrode (benchmark) which is close to zero. The dry electrode prototyped in this study is characterized to have a conductivity of 7 x 10 -4 S/mm, a resistance of 10 Ω, capacitive reactance of 140 Ω, and excellent signal stability showing a value of 256.5 μV consistently for 2 hours.